Totality In Architecture. Reflections on aesthetics and the coexistence of things with the place producing in us an experience of totality - Gallardo Frías, Laura (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
Today it is a revolution to talk about totality, —we refer to this concept as the quality of the total, the integrally thing— in such a fragmented world. Where are the teachings of Vitruvius of considering many things: the sky, the landscape, the stars... and today: our cities, its inhabitants, their context...? In this article, we revise diverse authors from different academic fields who dialogue through time. That is to say, we follow a sequence related with their ideas instead of their chronology. This allows dialectics about the importance of reflection in architectural projects through the object in itself to open thr discussion about considerations from other relevant aspects in order to continue thinking, and planning architecture with the purpose of generating a place and an experience of totality for its inhabitants.
Keywords: totality; architecture; aesthetic experience; coexistence; resonance